2003
DOI: 10.1046/j.1365-2370.2003.00382.x
|View full text |Cite
|
Sign up to set email alerts
|

Lack of association between transporter associated with antigen processing (TAP) and HLA‐DM gene polymorphisms and antibody levels following measles vaccination

Abstract: The transporter associated with antigen processing (TAP) and human leukocyte antigen-DM (HLA-DM) genes are involved in the antigen-processing pathway of both HLA class I and class II-restricted antigen presentation. We hypothesized that polymorphisms within the TAP and DM genes may influence antibody levels following measles vaccination. We examined TAP and DM polymorphisms in 242 school children from Olmsted County, Minnesota, USA who received one dose of measles-mumps-rubella-II (MMR-II) vaccine at the age o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…In the present study, we found that the frequency of DMB*01:07 was lower in the seropositive group than that in the seronegative group; however, the difference was not significant after FDR correction. Dhiman et al 37 studied the antibody response to the measles vaccine and did not identify an association between DMA and DMB alleles. Immunopeptidome analysis indicates that HLA‐DM allotypes may affect antigen presentation and CD4+ T cell activation 2 .…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we found that the frequency of DMB*01:07 was lower in the seropositive group than that in the seronegative group; however, the difference was not significant after FDR correction. Dhiman et al 37 studied the antibody response to the measles vaccine and did not identify an association between DMA and DMB alleles. Immunopeptidome analysis indicates that HLA‐DM allotypes may affect antigen presentation and CD4+ T cell activation 2 .…”
Section: Discussionmentioning
confidence: 99%
“…Several DM polymorphisms have been associated with predisposition to diseases such as Rheumatoid Arthritis (RA), Juvenile RA, medicamentosa-like Dermatitis, Primary Antiphospholipid Syndrome, Psoriasis and atopic Dermatitis (Toussirot et al, 2000;West and Reed, 1999;Yue et al, 2007;Sanchez et al, 2004;Pyo et al, 2003;Kuwata et al, 1996). Additionally, DM polymorphisms may influence vaccine responses (Dhiman et al, 2003;Ovsyannikova et al, 2004). However, no molecular mechanism behind these effects has been established yet and it is not known whether these polymorphisms alter the editing properties of DM.…”
Section: Naturally Occurring Polymorphisms In Immunopeptidome Editorsmentioning
confidence: 99%
“…immune disorders [33][34][35][36] or not at all [37][38][39][40]. Assigning a role for TAP polymorphism in disease susceptibility will require carefully powered studies with stratification of the data to control for linkage disequilibrium with other genes in the MHC class II region.…”
Section: Human Tap Polymorphism and Diseasementioning
confidence: 99%